Comparison of electrocautery and scalpel for blood loss and postoperative pain in Pfannenstiel incisions in recurrent cesarean sections: a randomized controlled trial - Eser Ağar; Gökhan Karakoç (IMR Press, 2021)
Background: Limited data is available on the use of cold-scalpel and electrocautery blades in Cesarean delivery (CD) operations. This randomized controlled trial aimed to compare their use for subcutaneous incisions in terms of blood loss and postoperative pain in women undergoing repeat CD. Methods: A total of 149 women scheduled for elective CD underwent spinal anesthesia, Pfannenstiel transverse skin incision with a cold-scalpel blade, and subsequent subcutaneous incisions until the peritoneum with a cold-scalpel or electrocautery blade. Perioperative blood loss and postoperative pain were evaluated. Results: The groups were similar in terms of maternal age, physical characteristics, and gestational age. The electrocautery group recorded significantly less blood loss and pain at the postoperative 6th and 12th hours. No significant correlation was found between blood loss or pain and women's physical characteristics or gestational age. Discussion: Perioperative and postoperative pain associated with CD is one of the predominant causes of anxiety in mothers. This study demonstrated that the use of electrocautery for subcutaneous incisions was associated with lower blood loss and lower postoperative pain compared to the cold-scalpel incisions in pregnant women undergoing repeat C-sections with Pfannenstiel incision. The study supports the recently shifting trend regarding the use of electrocautery instead of the scalpel.